Comportamento da atomização eletrotérmica de ouro, prata, bismuto, cádmio, chumbo e estanho em soluções aquosas e em etanol, a partir de diferentes superfícies atomizadoras - Silva,José Bento Borba da (2004)
The atomization behavior of Au, Ag, Bi, Cd, Pb, and Sn from pyrolitic graphite coating (L'vov platform) with the use Pd and Mg solutions, and zirconium coated platform with the analytes in nitric acid 0.2% v/v and in ethanol was investigated. In ethanol medium, the sensitivity gain was three-fold for Bi and Cd using Zr as modifier. Without modifier, the ethanol medium is appropriate only for Au and Cd. In nitric acid medium, the Zr coated platform elevates sensitivity at least two-fold for Bi and Cd. The method was applied to the determination of Ag, Au and Bi of certified steel samples, after on-line preconcentration, sorption on a minicolumn filled with C-18 bonded to silica gel and elution with ethanol. The concentrations obtained agreed with the recommended values.